2004
DOI: 10.1063/1.1739162
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistive study of the antiferromagnetic–weak ferromagnetic transition in single-crystal La2CuO4+δ

Abstract: The resistive measurements were made to study the magnetic field-induced antiferromagnetic (AF) -weak ferromagnetic (WF) transition in La2CuO4 single-crystal. The magnetic field (DC or pulsed) was applied normally to the CuO2 layers. The transition manifested itself in a drastic decrease of the resistance in critical fields of 5-7 T. The study is the first to display the effect of the AF -WF transition on the conductivity of the La2CuO4 single-crystal in the parallel -to -CuO2 layers direction. The results pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…which agrees with the previous data for La 2 CuO 4+δ [2,21,22]. The value of exponent (1/4) corresponds with that expected for a 3D system [23].…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…which agrees with the previous data for La 2 CuO 4+δ [2,21,22]. The value of exponent (1/4) corresponds with that expected for a 3D system [23].…”
Section: Resultssupporting
confidence: 91%
“…It should be noted that some of the authors of this article have observed more than once the R(T ) of La 2 CuO 4+δ (with T N in the range 180-280 K) behaving near T N as in Fig. 3 (e.g., see [2]). The study of Ref.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations